2013
DOI: 10.1097/mnm.0b013e328362d2fb
|View full text |Cite
|
Sign up to set email alerts
|

Estimated background doses of [67Ga]-DTPA-USPIO in normal Balb/c mice as a potential therapeutic agent for liver and spleen cancers

Abstract: High uptakes of USPIO nanoparticles in the liver and spleen and their fast clearance from other tissues suggest that these nanoparticles labeled with a β-emitter radioisotope could be suitable as treatment agents for spleen and liver malignancies only if the organ tolerance dose is not exceeded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Enriched 68 ZnCl 2 was irradiated at 30 MeV cyclotron (cyclone-30, IBA). Then, fifty microliters of ECC in absolute ethanol (1 mg/mL; 170 nmol) was added to the acidic solution (2 mL) of 67 GaCl 3 (111 MBq, 3 mCi) and vortexed at 90°C for 30-60 min in presence of 0.4 M sodium acetate buffer (pH 7, 4.5 mL) and normal saline (pH 4, 4.5 mL) [20,22]. 0.4 M sodium acetate:ethanol (7:3) mixture and/or 10 % ammonium acetate:methanol (1:1) mixture as the mobile phases were utilized as the mobile phases for radiochemical purity assessment.…”
Section: Preparation and Quality Control Of 67 Ga-eccmentioning
confidence: 99%
See 1 more Smart Citation
“…Enriched 68 ZnCl 2 was irradiated at 30 MeV cyclotron (cyclone-30, IBA). Then, fifty microliters of ECC in absolute ethanol (1 mg/mL; 170 nmol) was added to the acidic solution (2 mL) of 67 GaCl 3 (111 MBq, 3 mCi) and vortexed at 90°C for 30-60 min in presence of 0.4 M sodium acetate buffer (pH 7, 4.5 mL) and normal saline (pH 4, 4.5 mL) [20,22]. 0.4 M sodium acetate:ethanol (7:3) mixture and/or 10 % ammonium acetate:methanol (1:1) mixture as the mobile phases were utilized as the mobile phases for radiochemical purity assessment.…”
Section: Preparation and Quality Control Of 67 Ga-eccmentioning
confidence: 99%
“…In this case, extrapolation methods are applied to the values measured in the animal organs to have equivalent uptake in humans [14,15]. In continuation to previous experiences in estimation of human effective dose from rodents' data [10,[16][17][18][19][20][21][22][23][24] and to extend our previous study about 67 Ga-ECC [10], we attempted to compare the biodistribution data of intravenously (i.v.) injection of 67 Ga-ECC and 68 Ga-ECC as well as a prediction of the human absorbed dose of each tracer from mouse data.…”
mentioning
confidence: 99%
“…The distribution of a radiopharmaceutical varies not only from rodents to humans, but obviously also between rats and mice [43,44]. Extrapolation between various animal species is more reliable than extrapolation between animals and humans [32], but previous studies have demonstrated the utility of using animal distribution as a model for absorbed dose estimations in humans [21,45]. Using physiological time extrapolation improves the mean result.…”
Section: Discussionmentioning
confidence: 99%
“…In continuation to previous experiences in estimation of human effective dose from rodents' data [16][17][18][19][20][21][22] and to extend former studies [9,10,23], we attempted to compare the biodistribution data of intravenously (iv) injection of 67 Ga-DOTA-Gamma-aminobutyric acid (GABA)-Bombesin ( 67 Ga-BBN) and 99m Tc-hydrazinonicotinamide (HYNIC)-GABA-Bombesin ( 99m Tc-BBN) as well as a prediction of the human absorbed dose of each tracer from mouse data.…”
Section: Introductionmentioning
confidence: 92%
“…In parallel with SPION, another nanoparticle of SPION which has 20-40 nm diameters and called ultra-small super paramagnetic iron oxide (USPIO) is able to be coated with dextran. Studies show that After intravenously administration, dextrancoated USPIO have been exited from vascular system then they have been transferred to lymphatic system and absorbed by lymph nodes and in lymph nodes, dextrancoated USPIO have been accumulated in RES (macrophages) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%